Evaluation criteria of objects vibration state by parameters of signal characteristic function - I. S. Kudryavtseva; A. P. Naumenko; A. M. Demin (Омский научный вестник)
In operation, research results are presented in the field of technical diagnostics and are related to detection and examination of new faults diagnostic signs on the basis of vibroacoustic signal characteristic function parameters. The obtained signs are integral estimates of the vibroacoustic signals statistical characteristics for piston compressors. The paper presents the boundary values of diagnostic signs based on the parameters of the area under the curve of the vibroacoustic signals characteristic function modulus. The decision-making risk curves were constructed, the probabilities of missing a malfunction and a false alarm were calculated for the selected values of diagnostic signs. The use of suggested signs makes it possible to increase reliability of technical devices condition monitoring and their diagnosis.